2014
DOI: 10.1136/bmjopen-2014-004883
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for and perinatal outcomes of major depression during pregnancy: a population-based analysis during 2002–2010 in Finland

Abstract: ObjectivesTo identify risk factors for and the consequences (several adverse perinatal outcomes) of physician-diagnosed major depression during pregnancy treated in specialised healthcare.DesignA population-based cross-sectional study.SettingData were gathered from Finnish health registers for 1996–2010.ParticipantsAll singleton births (n=511 938) for 2002–2010 in Finland.Primary outcome measuresPrevalence, risk factors and consequences of major depression during pregnancy.ResultsAmong 511 938 women, 0.8% expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
152
0
33

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(198 citation statements)
references
References 31 publications
13
152
0
33
Order By: Relevance
“…Several previous studies have established parity and occupation as independent risk factors for PND [33,34]. Based on this study it can be suggested that expecting mothers should be encouraged to get engaged in some activities if they are having ample free time.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have established parity and occupation as independent risk factors for PND [33,34]. Based on this study it can be suggested that expecting mothers should be encouraged to get engaged in some activities if they are having ample free time.…”
Section: Discussionmentioning
confidence: 99%
“…Also, variables of age, relationship with spouse, consent of the husband's occupation, place of residence and place of receiving prenatal care were predictors of depression. Although, a history of depression is an important risk fac- tor for depression during pregnancy but half of women with no previous history of depression at pregnancy are affected (27). Psychosocial approaches including individual and group psychotherapy can be used for treatment of the most of patients with mild to moderate depression and these approaches are rather than drug therapy (28).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Depression and anxiety have been linked to somatic complaints, gestational and obstetric complications, stillbirth, premature birth, low birth weight, low Apgar scores, smaller head circumference, alterations in fetal motor activity, affected fetal heart rate patterns and major congenital anomalies. [3][4][5][6][7][8] Some studies found the prevalence of similar antenatal anxiety across all three trimesters, but many Previous studies reported that antenatal anxiety varied at different trimesters of pregnancy and high anxiety was found during first and third trimester. [9][10][11][12] Hence antenatal anxiety across trimesters can be of differing severity and different types of anxiety that may have differing consequences as morbidity.…”
Section: Introductionmentioning
confidence: 99%